2013
DOI: 10.1371/journal.pone.0078084
|View full text |Cite
|
Sign up to set email alerts
|

Talaromyces columbinus sp. nov., and Genealogical Concordance Analysis in Talaromyces Clade 2a

Abstract: During the course of mold surveys, a set of Talaromyces isolates were obtained that did not fit any described species. Phenotypic examination of these isolates showed that they were similar to T. piceus but differed in some growth characteristics. Multilocus DNA sequence data were obtained for the new isolates and some related species in the broader, more inclusive clade, and the data were analyzed using genealogical concordance. The new isolates are described as Talaromyces columbinus. From analysis of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Cultures were grown in duplicate as three-point inoculations in 9 cm diameter Petri dishes. Fungal isolation and microscopy were performed as described by Peterson & Jurjević (2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures were grown in duplicate as three-point inoculations in 9 cm diameter Petri dishes. Fungal isolation and microscopy were performed as described by Peterson & Jurjević (2013).…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from freeze-dried mycelium using the CTAB method (Peterson et al, 2015). Beta tubulin (BT2), calmodulin (CF), internal transcribed spacer region (ITS; containing ITS1, 5.8S rDNA and ITS2) and DNA-dependent RNA polymerase II second largest subunit (RPB2) were amplified from genomic DNA and sequenced using published methods (Peterson & Jurjević , 2013). Phylogenetic analysis of data sets from each locus was carried out with MEGA 6.06 (Tamura et al, 2013) using maximum-likelihood criterion and the model determined using the built-in model selection test routine.…”
Section: Methodsmentioning
confidence: 99%
“…Because not all the DNA regions were informative for differentiating all the fungal species observed, the DNA regions sequenced for each mycelial type were chosen based on previous phylogenetic analyses from taxonomic studies for the fungal genera observed (i.e., Athelia-like, Botrytis, Fusarium, Mucor, Neonectria, Penicillium, Phoma, Rhizopus, Sarocladium, and Talaromyces spp. ; [3][4][5]18,20,21,25,35,39,43,53,55,59,63). The isolates were each grown in potato dextrose broth (PDB; Becton Dickinson & Co.) on a DS-500E orbital shaker (VWR International, LLC, Aurora, CO; 100 rpm) at 21°C until a ball of mycelium (approximately 10 mm in diameter) was generated from the original 5-mm-diameter agar plug.…”
Section: Methodsmentioning
confidence: 99%
“…1 paper, placed in microcentrifuge tubes, frozen, and freeze-dried. Dry mycelium was ground to powder and rehydrated with cetyltrimethylammonium bromide buffer, proteins were extracted with chloroform, and nucleic acids were precipitated with isopropanol (27).…”
Section: Methodsmentioning
confidence: 99%
“…␤-Tubulin (BT2), calmodulin (CF), the nuclear ITS region, minichromosome maintenance factor (Mcm7), DNA-dependent RNA polymerase (RPB2), and pre-rRNA processing protein (Tsr1) were amplified with the primers and under the conditions specified by Peterson and Jurjevic (27). Amplified DNA was prepared for sequencing with ExoSapit (Affymetrix), sequencing reactions were carried out with BigDye ver.…”
Section: Methodsmentioning
confidence: 99%